A Short Media Training Session Is Effective in Reinforcing Psychiatrists’ Communication Skills About Suicide - Walter, Karl; Wathelet, Marielle; Valdenaire, Sacha; Grandgenèvre, Pierre; Pauwels, Nathalie; Vaiva, Guillaume; Notredame, Charles-Edouard (Frontiers in Psychology, 2021)
Because it has been associated with significant increases (through the Werther effect) or decreases (through the Papageno effect) of suicide rates, media coverage of suicide-related events is recognized as a prevention leverage. Unfortunately, the recommendations that the World Health Organization (WHO) has published to help journalists reporting on suicide remain poorly applied. The Mini Media Training (MMT) is a short media training session designed to increase psychiatrists’ ability to communicate about suicide during interviews. We aimed at assessing the effect of the MMT on psychiatrists’ ability to help journalists complying with the WHO recommendations. From June 2017 to December 2019, 173 physicians and residents in psychiatry we recruited during French national congresses. At baseline (T0) and one and three months later (T1), participants received the MMT, which consisted in a simulated interview where they we asked to answer a journalist about a fake suicide. Communication skills were measured with a score summing the number of delivered pieces of advice in relation to the WHO recommendations. A weighted score was also derived based on the degree of directivity needed for the participant to provide these items. A total of 132 psychiatrists participated in the study at T0 and T1. Both the weighted and unweighted scores significantly increased from T0 to T1. Having a history of contacts with journalists, a short professional experience and prior knowledge of the Werther effect, Papageno effect and WHO recommendations were significantly associated with greater unweighted and weighted scores at baseline. The latter two variables also predicted greater T0-T1improvement of the weighted score. These results suggests that the MMT could be effective for improving the ability of psychiatrists to guide journalists towards more responsible media coverage of suicide. As a short, easy to implement educational activity, the MMT could therefore be considered in association with other measures to help media professionals mitigating the WE and promoting the PE.